PENJADWALAN MESIN PADA SISTEM PRODUKSI FLOW SHOP UNTUK MEMINIMALKAN KETERLAMBATAN - Saputro, Irwan Adi; Mundar, Siti i (Heuristic, 2017)
The high rate of demand and the many type of products that have to be made, is a separate issue for PT Bioli Lestari. Delays in delivery of goods to consumers become a daily sight. Production scheduling in accordance with corporate characteristics needs. This research tries to find the method of scheduling according to the characteristics mentioned above. By the method of comparison between conventional method and repeated production scheduling method, ie Dannenbring method, Palmer method and Campbell Dudek Smith method, finally known that Dannenbring method resulted in the number of delayed work of 4 jobs with mean lateness of 8826.53 minutes medium Palmer method there are 5 jobs that are late With Mean lateness 4512.97 minutes, and on the Campbell Dudek Smith method the amount of work delayed were 4 jobs with mean lateness 9162 minutes. And the other side known that with conventional method there ware 9 jobs late. Based on that, then the corresponding method is Campbell Dudek Smith method with the number of jobs that are delayed ware 4 jobs and the mean lateness 9162 minutes.Keywords: scheduling, flow shop, tardyness, Repetitive Production.